Prototype of a Low Cost Turbine for the Generation of Clean Energy in the Ecuadorian Amazon - Guáitara, Bryan (2020)
Access to electricity supply in remote areas is limited, despite having wealth of other natural resources such as water. This document presents the design and construction of a scale electric generation system, taking advantage of the hydraulic energy produced by a constant flow of water flow. For this, the turbine design is described, which is based on the principles of Francis and Kaplan. In addition, the structural design made in CAD/CAM software and the actual implementation of the system are shown. To determine the generated electric potential, the electromagnetic analysis is performed based on the Maxwell-Faraday equation and the respective calculations. The validation of this proposal is determined by conducting experimental tests with balanced, unbalanced, series and parallel coils and with their implementation in a home. © 2020, Springer Nature Switzerland AG.